MODEL SISTEM CALL CENTER PADA UNIVERSITAS TRISAKTI - Zuhdi, Ahmad (Jurnal Teknik Elektro, 2004)
Call center is a common term for telephone-based human-service operation, currently hasbeen integrated with we enabled services. This paper will present, how to develop model foruniversity call center, to improve and fulfill the best services for all it stakeholder. Systemdevelopment begins with web based campus portal, since its complexity of the businessprocess on current system.Keyword: call center, business process analysis, system model.